Neonatal bacterial attack-unraveling the mysteries of acid defense - Rogers, Ian Munro (Journal of Neonatal Surgery, 2021)
This review article examines how gastric acidity develops and is maintained during the first 4 weeks of life. An initial maternal transfer of gastrin is followed by progressively increasing baby gastrin, not yet restrained by the rising acidity. When negative feedback matures at around 17 days, there is a predictable and real temporary peak acidity which is followed by controlled and independent baby acid secretion.